(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
One of the important sections of forensic medicine is forensic traumatology. It is devoted to the study of various mechanical injuries to the human body. Bodily injuries are violations of anatomical integrity or function of an organ [1].Sharp objects are characterised by the presence of a sharp edge , sharp end or both. sharp end and cause the occurrence of injuries both when acting normal to the body surface and at various angles [2]. At forensic examination of injuries by sharp and blunt objects a wide range of questions is solved, establishing the presence and nature of injuries, the type and features of the damaging object, the direction and number of movements or blows by the trauma instrument, the force of blows, the possibility of infliction of injuries by the victim himself, the position of his body at the time of injury [8]. Unfortunately, to date there is no clear definition of the concept of ‘brain injury’, revealing its content, scope and establishing its meaning [6].